2013
DOI: 10.1038/nature12862
|View full text |Cite|
|
Sign up to set email alerts
|

Pan-viral specificity of IFN-induced genes reveals new roles for cGAS in innate immunity

Abstract: The type I interferon (IFN) response protects cells from viral infection by inducing hundreds of interferon-stimulated genes (ISGs), some of which encode direct antiviral effectors1–3. Recent screening studies have begun to catalogue ISGs with antiviral activity against several RNA and DNA viruses4–13. However, antiviral ISG specificity across multiple distinct classes of viruses remains largely unexplored. Here we used an ectopic expression assay to screen a library of more than 350 human ISGs for effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
841
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 817 publications
(876 citation statements)
references
References 39 publications
29
841
6
Order By: Relevance
“…cGAMP then binds to stimulator of IFN genes (STING, also known as TMEM173, MITA, ERIS, or MPYS), which recruits and activates TANK-binding kinase 1 (TBK1) and IFN regulatory factor 3 (IRF3) to induce the expression of type I IFNs, which in turn induce expression of IFN-stimulated genes (ISGs). cGAS was reported to inhibit replication of DNA viruses such as Murid herpesvirus 68 (MHV-68), vaccinia virus, and herpes simplex virus 1 (HSV-1) (42,43). In this study, we find that the cytoplasmic isoforms of KSHV LANA interact with cGAS and antagonize its function in type I IFN signaling, thereby promoting the reactivation of KSHV from latency.…”
Section: Significancementioning
confidence: 65%
See 1 more Smart Citation
“…cGAMP then binds to stimulator of IFN genes (STING, also known as TMEM173, MITA, ERIS, or MPYS), which recruits and activates TANK-binding kinase 1 (TBK1) and IFN regulatory factor 3 (IRF3) to induce the expression of type I IFNs, which in turn induce expression of IFN-stimulated genes (ISGs). cGAS was reported to inhibit replication of DNA viruses such as Murid herpesvirus 68 (MHV-68), vaccinia virus, and herpes simplex virus 1 (HSV-1) (42,43). In this study, we find that the cytoplasmic isoforms of KSHV LANA interact with cGAS and antagonize its function in type I IFN signaling, thereby promoting the reactivation of KSHV from latency.…”
Section: Significancementioning
confidence: 65%
“…To address the biological significance of this observation, we took advantage of the observation that cGAS can restrict HSV-1 replication (42,43). We infected the LANA FL and LANAΔ161 expressing HeLa MZ cell lines with HSV-1 at an MOI (multiplicity of infection) of 0.1 and measured the levels of newly produced viral progeny in the cell culture supernatant by plaque assay on Vero cells.…”
Section: Significancementioning
confidence: 99%
“…irf3 −/− mice show no defect in peripheral control of HSV-1 administered by the intravenous route (36) or the corneal route (37), but irf3 −/− mice showed more central nervous system disease and viral replication than WT mice (37). Two independent reports have characterized two lines of cgas −/− mice to determine its role in vivo: Li et al (13) reported that cgas −/− mice showed decreased IFN responses and were more susceptible to HSV-1 infection by the intraperitoneal route, and Schoggins et al (38) demonstrated that cgas −/− mutations resulted in a down-regulation of basal IFN and resulted in increased RNA and DNA virus replication, including murine herpesvirus 68, indicating that the antiviral activity of cGAS is not specifically tied to DNA virus infection. Because there are no data on peripheral HSV clearance in the cgas −/− mice, more studies are needed to determine if IRF-3 and cGAS knock-out mice are consistent in their phenotypes with regard to HSV-1 pathogenesis.…”
Section: Roles For Both Ifi16 and Cgas In Innate Responses In Transfementioning
confidence: 99%
“…Caspase-1 −/− , AIM2 −/− , NLRP3 −/− , ASC −/− , and cGAS −/− mice on a C57BL/ 6J background were previously described (24,72,73). Mice were bred in the Center of Infection and Immunity animal facility at the University of Lausanne or at the Plateau De Biologie Expérimentale De La Souris (Lyon, France).…”
Section: Methodsmentioning
confidence: 99%